Categorização functional trófica das comunidades de macroinvertebrados de dois reservatórios na região centro-oeste do Estado de São Paulo, Brasil - da Silva, Fabio Laurindo; Pauleto, Gustavo Mayer; Talamoni, Jandria Liria Biscalquini [UNESP]; Ruiz, Sonia Silveira [UNESP] (Universidade Estadual de Maringa, 2009)
The use of the concept of guild can be useful for the functional trophic categorization of communities, because there is no requirement identification of organisms in the level of species and not to treat each species as a separate entity. The aim of this study was to analyze the functional feeding groups (collectors-gatherers, collectors-filterers, shredders, predators and grazer-scrapers) of the macroinvertebrate communities of two reservoirs in the Midwestern region of São Paulo State. Sampling was carried out in rainy (March/April - 2001) and dry (July/August - 2001) seasons and the data obtained indicate that 'collectors-gatherers' is the most frequent guild. This fact suggests a great importance of organic matter as a food source in the diet of the macroinvertebrates analyzed.
Functional trophic categorization of macroinvertebrate communities of two reservoirs in the midwestern region of São Paulo State, Brazil
Keywords: Estação Ecológica de Caetetus; Functional feeding groups; Guilds; Parque zoológico municipal de Bauru; organic matter; animal community; animal experiment; animal food; Brazil; controlled study; macroinvertebrate; nonhuman; organismal interaction; seasonal variation; taxonomic identification; trophic level